The emerging role of jasmonate in the control of flowering time. (2nd October 2021) - Zhao, Lirong; Li, Xia; Chen, Wanqin; Xu, Zhiyu; Chen, Mifen; Wang, Houping; Yu, Diqiu
Abstract: Plants dynamically synchronize their flowering time with changes in the internal and external environments through a variety of signaling pathways to maximize fitness. In the last two decades, the major pathways associated with flowering, including the photoperiod, vernalization, age, autonomous, gibberellin, and ambient temperature pathways, have been extensively analyzed. In recent years, an increasing number of signals, such as sugar, thermosensory, stress, and certain hormones, have been shown to be involved in fine-tuning flowering time. Among these signals, the jasmonate signaling pathway has a function in the determination of flowering time that has not been systematically summarized. In this review, we present an overview of current knowledge of jasmonate control of flowering and discuss jasmonate crosstalk with other signals (such as gibberellin, defense, and touch) during floral transition. Abstract : This review provides new insights into the jasmonate pathway and its crosstalk with other signaling pathways in regulating flowering time.